Unified Bernstein and Bleimann-Butzer-Hahn basis and its properties - Özarslan, Mehmet Ali; Bozer, Mehmet (Springer International Publishing AG, 2013)
In this paper we introduce the unification of Bernstein and Bleimann-Butzer-Hahn basis via the generating function. We give the representation of this unified family in terms of Apostol-type polynomials and Stirling numbers of the second kind. More generating functions of trigonometric type are also obtained to this unification. MSC: 11B65, 11B68, 41A10, 30C15.
The file in this item is the publisher version (published version) of the article.
Keywords: Euler polynomials, generating function, Functional Analysis, Bernstein polynomials; Mathematics, Difference and Functional Equations, Bernoulli polynomials; Partial Differential Equations, Stirling numbers of the second kind, Analysis, Ordinary Differential Equations; Generating function, Functions, Continuous, Inequalities (Mathematics), Difference equations, Euler angles, Usage